Socioeconomic determinants of HIV prevalence among women in Eswatini: A cross-sectional study - Cuilan Wang (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
Eswatini records the world's highest HIV burden, with female HIV prevalence markedly elevated compared to males. Understanding the socioeconomic structural drivers of this epidemic is essential for evidence-based prevention policy. This cross-sectional longitudinal study used secondary annual data from the World Development Indicators (WDI) database (World Bank, 2000–2022; n=23 annual observations) to examine the effects of female unemployment (FUMP), female secondary school enrolment (EDU), urban population share (URB), and income inequality (GINI) on female HIV prevalence (HIVP). A three-stage analytical approach was employed: descriptive statistics, graphical co-movement trend analysis, and multivariable Ordinary Least Squares (OLS) regression to identify independent predictors of female HIV prevalence while controlling for confounding. Female HIV prevalence declined from 16.0% in 2000 to 8.2% in 2022. The multivariable OLS regression revealed that female secondary school enrolment (β=−0.103, p<0.001) and female unemployment (β=−0.194, p<0.001) are the dominant independent predictors of female HIV prevalence. Income inequality exerted a positive effect (β=+0.594, p=0.074), while urbanization was negatively associated (β=−1.237, p=0.069). Female secondary school enrolment and female unemployment are the dominant socioeconomic determinants of HIV prevalence among women in Eswatini. Integrated policies combining education investment, economic empowerment, and income inequality reduction are essential for sustainable HIV prevention.